Bactericidal killing of meningococcal W strains isolated in Argentina by the sera of adolescents and infants immunized with 4-component meningococcal serogroup B vaccine (4CMenB) - Adriana Efron; Alessia Biolchi; Cecilia Sorhouet Pereira; Sara Tomei; Josefina Campos; Denise De Belder; María Alicia Moscoloni; Mauricio Santos; Gabriela Vidal; Florencia Nocita; Carla Vizzotti; Mariagrazia Pizza (Taylor & Francis Group, 2023)
ABSTRACTInvasive meningococcal disease (IMD) is a life-threatening disease caused by meningococcal serogroups A, B, C, W, X, and Y, of which B and W are most common in Argentina. The 4-component meningococcal serogroup B (4CMenB) vaccine contains three purified recombinant protein antigens (Neisseria adhesin A [NadA], factor H binding protein [fHbp], and Neisserial Heparin Binding Antigen [NHBA]) and outer membrane vesicles (OMV), which is derived from the New Zealand epidemic strain and contains Porin A 1.4. These antigens are present and conserved in strains that belong to other serogroups. In this study, we show that 10/11 (91%) meningococcal serogroup W (MenW) strains selected to be representative of MenW isolates that caused IMD in Argentina during 2010-2011 were killed in bactericidal assays by the sera of adolescents and infants who had been immunized with the 4CMenB vaccine. We also show that MenW strains that caused IMD in Argentina during 2018-2021 were genetically similar to the earlier strains, indicating that the 4CMenB vaccine would likely still provide protection against current MenW strains. These data highlight the potential of 4CMenB vaccination to protect adolescents and infants against MenW strains that are endemic in Argentina.